Ivan Petrovich Pavlov - is a creator studies about physiology of digestion - Voloshchuk, V. M.; Yudina, K. Ye. (History of science and technology, 2014)
The article is sanctified to scientific achievements of large scientist-physiologist Ivan Petrovich Pavlov. Basic achievements of research worker are reflected. Drawn conclusion in relation to meaningfulness of researches for further development of physiology science. Due to I.P. Pavlov and his numeral students and teachers physiology of digestion is legally acknowledged by the domestic division of physiology. During all life he fruitfully and insistingly worked in the most difficult and the least investigational directions of physiology and was an innovator and revolutionary in science. Scientific achievements of I.P.Pavlov had an enormous influence on the study of physiology of digestion of animals. His labours from imposition by the animal of permanent fistula of pancreas, studies of secretion of juice a stomach by means of the so-called "imaginary feeding" and creation of the "isolated ventricle" was accomplish the real revolution in physiology of that time and remain actual and now. A scientist is the author of difficult surgical methods, which provides possibility to conduct long time on an animal, which got better after operative intervention, supervision in natural or small changed terms. His researches had not only a theoretical value but also practical. They enabled to perfect the ration of agricultural animals for the receipt of considerable increase of mass of body, to perfect the terms of maintenance and feeding of animals.